Diet quality and 10‐year healthcare costs by BMI categories in the mid‐age cohort of the Australian Longitudinal Study on Women's Health. Issue 4 (17th April 2018) - Patterson, A.; Hure, A.; Burrows, T.; Jackson, J.; Collins, C.
Abstract: Background: Better diets, as evaluated by diet quality indices, are associated with lower rates of morbidity and mortality. Although governments and researchers alike recognise the burden that obesity incurs for increased healthcare spending, there is insufficient evidence for the role of diet quality on healthcare costs. Methods: Diet quality was assessed by the Australian Recommended Food Score (ARFS) for 6328 women aged 50–55 years from the Australian Longitudinal Study on Women's Health. The ARFS was ranked by quintile, and 10‐year cumulative data on healthcare costs from Medicare (Australia's Universal healthcare cover) were reported by body mass index category, using generalised linear modelling. Results: Healthy weight women with the highest diet quality were found to make significantly fewer Medicare claims ( P = 0.012) compared to those with the lowest diet quality. In healthy weight and overweight women, the number of healthcare claims and charges was inversely associated with consuming a greater variety of vegetables. For every 1 point increase in the ARFS vegetable component score, healthy weight women made 1.9 fewer healthcare claims and were charged $139 less, whereas overweight women made 2.3 fewer claims and were charged $176 less for healthcare over 10 years. Conclusions: The results of the present study support the need to prioritise an improved diet quality with the aim of reducing healthcare claims and overall costs in a population‐based sample of Australian females. As the burden of overweight and obesity on the healthcare system increases, strategies to improve diet quality may be of particular importance; however, more research is required to further establish this relationship.